2000
DOI: 10.1037/0894-4105.14.2.224
|View full text |Cite
|
Sign up to set email alerts
|

The cognitive correlates of white matter abnormalities in normal aging: A quantitative review.

Abstract: Cerebral white matter of asymptomatic people frequently exhibits circumscribed areas of hyperintensity on magnetic resonance (MR) images and hypodensity on computed tomography scans. However, behavioral implications of this phenomenon remain unclear. In this meta-analysis, the authors examine cumulative evidence regarding the cognitive sequelae of white matter abnormalities in adults without dementia. The influence of potential moderator variables, such as neuroimaging technique, location of the lesions, ratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
468
7
6

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 643 publications
(516 citation statements)
references
References 31 publications
35
468
7
6
Order By: Relevance
“…The Very-Old control participants performed significantly worse than the Young-Old control participants on nearly all of the cognitive tests, with the largest differences apparent on tests of memory, executive functions, and category fluency. These findings are consistent with previous reports of the adverse effects of normal aging on these cognitive abilities (Corey-Bloom et al, 1996;Gunning-Dixon & Raz, 2000;Hulette et al, 1998;Mittenberg et al, 1989). It is important to note that this decline in cognitive ability was evident in the Very-Old NC group despite largely excluding individuals who may have been in a preclinical stage of AD.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The Very-Old control participants performed significantly worse than the Young-Old control participants on nearly all of the cognitive tests, with the largest differences apparent on tests of memory, executive functions, and category fluency. These findings are consistent with previous reports of the adverse effects of normal aging on these cognitive abilities (Corey-Bloom et al, 1996;Gunning-Dixon & Raz, 2000;Hulette et al, 1998;Mittenberg et al, 1989). It is important to note that this decline in cognitive ability was evident in the Very-Old NC group despite largely excluding individuals who may have been in a preclinical stage of AD.…”
Section: Discussionsupporting
confidence: 91%
“…A number of studies have shown that normal aging is associated with mild brain atrophy on structural magnetic resonance (MR) imaging (Jack et al, 1998a(Jack et al, , 1999Jernigan et al, 2001;Pfefferbaum et al, 1994), decreased hemodynamic response on functional MR imaging (D'Esposito et al, 1999), reduced synaptic density (Masliah et al, 1993), increased white matter abnormalities (Guttman et al, 1998;Jernigan et al, 2001;Salat et al, 1999), and a subclinical accumulation of neuritic plaques and neurofibrillary tangles in medial temporal lobe brain regions (Green et al, 2000;Hulette et al, 1998). These brain changes are accompanied by age-related declines in information processing speed, executive functions, and efficiency of learning and recall (Corey-Bloom et al, 1996;Desgranges et al, 1998;Grady et al, 1995;Gunning-Dixon & Raz, 2000;Hulette et al, 1998;Mittenberg et al, 1989;Schacter et al, 1996;Ylikoski et al, 1993). The structural and functional decline that occurs in the Very-Old has led some investigators to suggest that less AD pathology may be needed to produce pathologic cognitive decline in the Very-Old compared to the Young-Old (see .…”
Section: Introductionmentioning
confidence: 99%
“…These findings were established with the canonical correlation analysis used for our study. Previous studies have investigated the relationship between WMHs and cognitive decline in nondemented and demented elderly [18,[34][35][36][37][38]. Cognitive test scores in older adults were found to be worse in the presence of severe WMHs, even after adjustments for age, gender and education [18].…”
Section: Discussionmentioning
confidence: 99%
“…6,7 However, identification of the neural components involved in age-related functional decreases has yet to be performed. Even though significant shrinkage in cortical gray matter volume occurs through adulthood, 8 primarily occurring in frontal regions, 9 MR spectroscopy and spectroscopic imaging suggest that gray matter remains viable and relatively resistant to aging, and that concentrations of gray matter metabolites (such as n-acetylaspartate) are stable with increasing age.…”
Section: Mri and Agingmentioning
confidence: 99%